2008
DOI: 10.1007/s11357-007-9045-9
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome-targeted stress reveals increased stability of lipofuscin-containing lysosomes

Abstract: Cellular ageing is associated with accumulation of undegradable intralysosomal material, called lipofuscin. In order to accelerate the lipofuscin accumulation, confluent, growth-arrested human fibroblasts were cultured under hyperoxic conditions. To provide a better insight into the effects of lipofuscin on cellular functions, we compared lysosomal stability in control and lipofuscin-loaded human fibroblasts under conditions of lysosometargeted stress induced by exposure to either the lysosomotropic detergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Under normal conditions, cathepsin D is found only in endosomes/lysosome . The permeabilization of endosomes/lysosomes’ membrane could cause the release of this protein. , In this study, the results of Western blotting indicated that this type of release was significantly higher in the cytoplasmic fractions of MCF-7/ADR cells after treatment of conjugates compared to free DOX (Figure A), providing the evidence that the integrity of endosomes/lysosomes was destabilized to a greater extent in the presence of T10-DOX and T15-DOX. Since the released cathepsin D in cytosol can further initiate apoptosis signaling pathways, apoptosis-related caspase-3 protein expression was measured.…”
Section: Resultssupporting
confidence: 54%
“…Under normal conditions, cathepsin D is found only in endosomes/lysosome . The permeabilization of endosomes/lysosomes’ membrane could cause the release of this protein. , In this study, the results of Western blotting indicated that this type of release was significantly higher in the cytoplasmic fractions of MCF-7/ADR cells after treatment of conjugates compared to free DOX (Figure A), providing the evidence that the integrity of endosomes/lysosomes was destabilized to a greater extent in the presence of T10-DOX and T15-DOX. Since the released cathepsin D in cytosol can further initiate apoptosis signaling pathways, apoptosis-related caspase-3 protein expression was measured.…”
Section: Resultssupporting
confidence: 54%
“…Many studies have reported the negative effects of accumulating lipofuscin on lysosomal activity and cellular function, but more recent studies have suggested that lysosomes can play a protective role in the oxidative stress response and suggest that lipofuscin accumulation is indicative of cellular maintenance through autophagic activity [26,27,37]. In sea urchins, an age-related accumulation of lipofuscin was seen in all tissues examined (muscle, nerve and esophagus) which reaches significance in muscle tissue of L. variegatus and S. purpuratus , esophagus tissues of S. purpuratus and nerve tissue of all three species.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal stability was assessed by red AO-fluorescence, using Image-Pro Plus 6.0 software (Media Cybernetics, Rockville, MD, USA, 2006). Fluorescence intensity was expressed in arbitrary units: average pixel value per lysosome or the lysosome area [ 33 ].…”
Section: Methodsmentioning
confidence: 99%